Structural insights into carboxylic polyester-degrading enzymes and their functional depolymerizing neighbors - Leitão, Ana Lúcia (2021)
Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative CommonsAttribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).